Formação do professor de educação infantil: mediação das tecnologias digitais da informação e comunicação (TDIC’s) na perspectiva da educomunicação - Junqueira, Cinthia Faria (2022)
This work aims to know and analyze the relationship between the early childhood education teacher in an environment permeated by DICT and how it would be possible to work with DICT from the perspective of educommunication. In such a context, we intend to contribute to the formation of teachers who seek to implement educommunicative practices in their classes, especially early childhood education teachers, with students between the age group of four to six years. We present the relevance of the identification of the early childhood education teacher in face of his communicational action in an environment mediated by digital information and communication technologies (DICT), and how it is possible to work with the DICT in early childhood education from the perspective of educommunication. Therefore, among these aspects, we have the study and analysis of the role of the early childhood education teacher in an environment mediated by digital information and communication technologies, the importance of using DICT as means of facilitating the communication process in the pedagogical act from the teacher in early childhood education, in addition to analyzing and presenting the importance of educommunication as a pedagogical practice in early childhood education. Thus, as a product of the present research, a tutorial was developed that will be distributed electronically, under the title: Tutorial on Educommunication in Early Childhood Education. Its intention is to be an instrument to help the teacher to create his or her own educommunicative ecosystem, presenting ways to use educommunication in early childhood education; proposing means and activities to be applied; indicating contents and tips through hyperlinks. The research follows a qualitative approach, with a descriptive objective and bibliographical bias. It has theoretical basis in authors who approach themes such as educommunication and digital technologies applied in the educational scope; such as José Manuel Moran, Ismar de Oliveira Soares, Maria Aparecida Baccega, Marilda Aparecida Behrens, Marcos Tarciso Masetto, Vani Moreira Kenski, among others.